Characterizing nonlinear dynamic features of self-sustained thermoacoustic oscillations in a premixed swirling combustor. (15th April 2020) - Sun, Yuze; Rao, Zhuming; Zhao, Dan; Wang, Bing; Sun, Dakun; Sun, Xiaofeng
Graphical abstract: Highlights: Nonlinear dynamics of a swirling thermoacoustic combustor is characterized. Effects of fuel-air equivalence ratio are studied on generating thermoacoustic instability. Periodic limit cycle and period-doubling bifurcation is experimentally found. 'Kick-oscillator' model is developed to capture deterministic and chaotic natures. Recurrence analysis is performed to characterize nonlinear dynamics of combustion instability. Abstract: To meet stringent NOx emission requirements, lean premixed swirling combustion technology is widely applied in power generation and propulsion systems. However, such combustion systems are more susceptible to nonlinear combustion instability due to the fluid flow-acoustics-combustion interaction. It is typically self-exited and characterized by large-amplitude pulsating oscillations. By applying experimental measurements and theoretical modelling, we explore the rich physics of how a methane-burnt swirling flame sustains periodic pulsating combustion oscillations, and its nonlinear dynamics features via recurrence plots (RP) and 0–1 chaotic test. The effects of (1) the equivalence ratio Φ, (2) the volume flow rate Va of inlet air and (3) the swirling number SN are examined. Hopf Supercritical and period-doubling bifurcation behaviours are experimentally observed with increased Φ from lean to rich combustion. Same nonlinear features are theoretically modelled by using 'kick-oscillator' model representing combustion pulses and to capture periodic limit cycle behaviours followed by period-doubling bifurcation and transition to chaos. The deterministic or chaotic nature of the swirling combustor could be experimentally identified using classical approaches such as probability density functions (PDFs) and acoustics power spectrum in presence of combustion-sustained periodic fluctuations and 0–1 chaotic test method. When the combustor is experimentally operated under either lean (Φ ≤ 0.6) or rich (Φ ≥ 1.1) conditions, no self-sustained periodic acoustic fluctuations are generated. Furthermore the combustor is found to be more chaotic. The flame shapes (M- or V-shaped), colour, brightness and volumes are found to depend on SN strongly. The present findings are physically insightful on understanding nonlinear features of swirling flow-acoustics-flame interaction.